Procalcitonin for Antibiotic Prescription in Chronic Obstructive Pulmonary Disease Exacerbations: Systematic Review, Meta-Analysis, and Clinical Perspective - Chen, Ken (Pulm Ther, 2020)
The 2020 Global Initiative for Obstructive Lung Disease report indicates that the blood biomarker procalcitonin (PCT) may assist in decision-making regarding the initiation of antibiotics for chronic obstructive pulmonary disease (COPD) exacerbations. PCT is an acute-phase reactant that increases in response to inflammation and infection, and has been studied in various bacterial infections for initiation and de-escalation of antibacterials. The purpose of this systematic review and meta-analysis was to evaluate the strength of the data on the use of PCT to guide antibiotic prescription in COPD exacerbations. Among the randomized clinical trials included in our meta-analysis, almost all of which were conducted exclusively in the hospital setting. PCT was found to decrease overall antibiotic exposure in COPD exacerbations by 2.01 days (p = 0.04), while no apparent effects were found on clinical outcomes (length of hospital stay, p = 0.88; treatment failure p = 0.51; all-cause mortality p = 0.28). However, the majority of blood PCT levels in COPD exacerbations were below the manufacturer-recommended cutoff for antibiotics, and the use of this marker was associated with worse outcomes in the intensive care setting. Further, based on additional sensitivity analysis excluding studies with high risk of bias or with converted outcome value, the effect of PCT on antibiotic duration in RCTs was no longer significant (MD = −1.88 days, 95% CI [−3.95, 0.19] days, p = 0.08, and MD = −1.72 days, 95% CI [−4.28, 0.83] days, p = 0.19, respectively). Our review and analysis does not support the use of PCT to guide antibiotic prescription in COPD exacerbations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s41030-020-00123-8) contains supplementary material, which is available to authorized users.